Morphological Analysis of Quiescent and Activated Keratocytes: A Review of Ex Vivo and In Vivo Findings. (December 2014) - Hovakimyan, Marina; Falke, Karen; Stahnke, Thomas; Guthoff, Rudolf; Witt, Martin; Wree, Andreas; Stachs, Oliver
Abstract Keratocytes are specialized, neural crest-derived mesenchymal cells occupying approximately 3% of the corneal stromal volume. They reside between the collagen lamellae and are responsible for the secretion of extracellular matrix macromolecules, thus contributing to the corneal transparency and integrity. During the regeneration process after infection, traumata and refractive surgery, the keratocytes undergo transition into divergent phenotypes, which are referred to as "activated keratocytes". Quite shortly after injury, the keratocytes lose their quiescence, enter into the cell cycle and migrate toward the site of injury. In certain types of injury, which affect the integrity of basement membrane, activated keratocytes also participate in wound closure by production of α-smooth muscle actin (α-SMA). Since the activated keratocytes are the major cell type contributing to tissue repair during corneal wound healing, their morphological and biochemical properties have been studied in details in experimental studies using light and electron microscopy. More recently, emerging of in vivo microscopy techniques has opened new possibilities to investigate cornea in vivo. The non-invasive nature of this imaging modality enables repeated examination of the same tissue over time and is an ideal tool to rapidly and accurately investigate corneal wound healing. However, the in vivo data on activated keratocytes are not as uniform as data from experimental ex vivo studies. There is still inconsistency in the literature findings on activated phenotypes, and often the described morphologies cannot be appreciated in in vivo images. In this article, a literature review was performed in order to interpret the morphology of different activated phenotypes, based on biological processes underlying the morphological alterations.